1966
DOI: 10.1177/004051756603601205
|View full text |Cite
|
Sign up to set email alerts
|

The Behavior of Fabrics in Shear

Abstract: A new instrumental method for the analysis of the stress-strain behavior of fabrics in shear has been designed which utilizes the Instron and its automatic recording. It is similar in principle to the laboratory method previously employed by Treloar. A cotton and a spun viscose fabric were investigated for their dependence of shear properties on specimen shape and normal stress. The range of variables previously investigated by Treloar has been extended to include specimen shapes corresponding to length: width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1967
1967
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Behre [1 ] applied the small-strain theory to these two tests and observed the considerable importance of the test conditions in determining the results. However, he employed a rather unadvantageous square specimen in simple shear [8,9], and his results may be subject to some uncertainty for that reason. In an attempt to define theoretically the planar stress-strain relationships of woven fabrics, Weissenberg [10] introduced the trellis type of mechani-. cal model, with the assumptions of inflexible and inextensible threads, pinpointed at their nodal points, with lines of zero elongation.…”
Section: Equivalent Shear Stressmentioning
confidence: 99%
“…Behre [1 ] applied the small-strain theory to these two tests and observed the considerable importance of the test conditions in determining the results. However, he employed a rather unadvantageous square specimen in simple shear [8,9], and his results may be subject to some uncertainty for that reason. In an attempt to define theoretically the planar stress-strain relationships of woven fabrics, Weissenberg [10] introduced the trellis type of mechani-. cal model, with the assumptions of inflexible and inextensible threads, pinpointed at their nodal points, with lines of zero elongation.…”
Section: Equivalent Shear Stressmentioning
confidence: 99%
“…Data were obtained for ten filament samples from each of the .two specimens, and a comparison of the results showed that heat-setting caused the filaments to contract by approximately 5.5%. ' Effect of Setting-Temperature Oil the Shear Properties of the Fabric All shear measurements on the fabrics were made on the instrument and by the method described in an earlier paper [ 15 ] . The shear parameters employed in this earlier work will also be continued here.…”
Section: Experimental and Resultsmentioning
confidence: 99%
“…Values of tan 91 and tan d2 were used, tan 91 being obtained from the known initially applied shear strain and tan 62 calculated from the resulting mean decrement. The values of cyclical energy loss were then compared with the cyclical energy loss obtained in experiments by the sf atic method 15 ] Table IV is a summary of the cyclical energy loss values obtained by the two methods and for the unset and heat-set specimens investigated. Two values of normal stress for the heat-set specimen are presented, while only the higher of the two for the unset specimen as its greater energy loss and damping make accurate recording difbcult at lower normal stresses.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations